2018
DOI: 10.3390/coatings8020053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation and Modeling of the Damping Properties of Multi-Layer Coated Composites

Abstract: Abstract:In this work, the dissipative properties of different coating solutions are compared and a beam mechanical model, taking into account of dissipative actions at the interface between different layers is proposed. The aim is to find optimal coatings to be employed in the production of composites with high damping properties. The investigated coating layers are obtained from different materials and production processes, and are applied on different metallic substrates. The composite specimens, in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…By substituting the properties of the measured test specimen given in Table 1 into the Eqs. (9)(10)(11) the first, second, and third natural frequencies become 39.73 Hz, 249 Hz, and 702.79 Hz. By comparing with the experimental values of the cantilever beam it is concluded that analytical values are quite close to the experimental values.…”
Section: Results and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…By substituting the properties of the measured test specimen given in Table 1 into the Eqs. (9)(10)(11) the first, second, and third natural frequencies become 39.73 Hz, 249 Hz, and 702.79 Hz. By comparing with the experimental values of the cantilever beam it is concluded that analytical values are quite close to the experimental values.…”
Section: Results and Analysismentioning
confidence: 98%
“…Enhancement in vibration damping is observed in both cases but hard coating material (alumina) showed more improvement in damping. Amadori et al [11] compared the damping properties of hard coating made by an anodizing process and by a reactive plasma vapor deposition process. Hard-coated specimens showed improvement in damping compared to un-coated specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory alloy actuators are known to have a simple operating mechanism, be quiet, excellent repeatability with little hysteresis, and small aging effect. On the other hand, since the actuator operates on thermal energy, the energy efficiency is low, bandwidth is limiting, and response time is rather slow (Amadori et al, 2018; Kim, 2012; Urreta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Coatings can be employed to increase the global dissipative properties of a mechanical component with limited influence on the other mechanical properties. Mechanical components with high stiffness, thermal resistance and vibration damping specifications are in great demand for most mechanical engineering applications [4] The coated component dissipative properties can be significantly tailored by means of the application of coating layers with high internal hysteresis or with high frictional actions at the interface between the different layers.…”
Section: Introductionmentioning
confidence: 99%